Factors associated with contraceptive use among women of reproductive age in rural districts of Burkina Faso - Wulifan, Joseph K.; Mazalale, Jacob; Jahn, Albrecht; De Allegri, Manuela (Journal of health care for the poor and underserved, 2017)
Given the current low contraceptive use and corresponding high levels of unwanted pregnancies leading to induced abortions and poor maternal health outcomes among rural populations, a detailed understanding of the factors that limit contraceptive use is essential. Our study investigated household and health facility factors that influence contraceptive use decisions among rural women in rural Burkina Faso. We collected data on fertile non-pregnant women in 24 rural districts in 2014. Of 8,657 women, 1,098 used a modern contraceptive. Women having a living son, a child younger than one year, and household wealth were more likely to use modern contraceptives. Women in polygamous marriages and women living at least 5 kilometers from a health facility were less likely to use contraception. We conclude that modern contraceptive use remains weak, hence, programs aiming to encourage contraceptive use must address barriers at both the health facility and the household level.